The resilience of the city of Dublin to flooding: from theory to practice - Serge Lhomme (Unité Mixte de Recherche 8504 Géographie-cités, 2019)
On the one hand Dublin is exposed to flooding and on the other hand Dublin’s urban development requires urbanizing flood-prone areas. That is why, in order to cope with floods, city managers claim to implement new actions to improve the resilience of their territory. At the same time, resilience raises many academic debates on its definitions and operational relevance. Thus, this article shows that resilience elusiveness raises operational issues. Moreover, the absence of a systemic approach of Dublin flood risk management, highlighted by a technical networks resilience analysis, illustrates the difficult consideration by practitioners of a non-stabilized concept in the academic field.Keywords: resilience, risk management, flood, technical network